Implementation of DSP-based matrix converter using space vector modulation algorithm - Erdem, E.; Tatar, Y.; Sunter, S. (Proceedings : International Aegean Conference on Electrical Machines and Power Electronics & Electromotion : joint conference, Bodrum Turkey, 10-12 September 2007, 2007)
In this paper; simulation, design, and implementation of space vector controlled three-phase to three- phase matrix converter have been presented. A Simulink model has been developed in such a way that it supports real time work with the use of DSP control card supported by Simulink. Space vector control algorithm has been preferred to the other control algorithms since it is easy to implement and to control the input power factor with reduced switching loses. Simulation and experimental results of the input and output waveforms of the matrix converter for R-L load are given at various operating conditions. Good agreement was obtained between simulation and laboratory experiments.